Respuesta :

Answer:

Step-by-step explanation:

f(x)=-2x³+x-3

-f(x)=2x³-x+3

f(-x)=-2(-x)³+(-x)-3

=2x³-x-3

it is not equal to f(x) or -f(x)

so it is neither even or odd.

[tex]f(x)=\frac{x+5}{x} \\f(-x)=\frac{-x+5}{-x} =\frac{x-5}{x} \\it ~is~neither~equal~to~f(x)~or~-f(x)\\[/tex]

it is neither even or odd.

f(x)=x^4-x^2+10

f(-x)=(-x)^4-(-x)^2+10=x^4-x^2+10=f(x)

it is an even function.

[tex]f(x)=\frac{5}{-x^2+1} \\f(-x)=\frac{5}{-(-x)^2+1} =\frac{5}{-x^2+1} =f(x)\\[/tex]

it is an even function.

[tex]f(x)=\frac{-2}{5x} \\f(-x)=\frac{-2}{-5x} =\frac{2}{5x} =-f(x)\\it~ is ~an ~odd ~function.\\[/tex]

f(x)=x^9-x^5+4x^3

f(-x)=(-x)^9-(-x)^5+4(-x)^3

=-x^9+x^5-4x^3

=-(x^9-x^5+4x^3)

=-f(x)

it is an odd function.